Analisis isi Pesan Dakwah Studi Kasus Pada Majalah tanwirul afkar edisi 564 tahun 2023 “Musuh Baru Para Buruh” - Nadia; Hasyim; Assilah, Qonita (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This research aims to analyze the content of the da'wah message in Tanwirul Afkar magazine, edition 564 in 2023 with the theme